Students’ Conceptions of Learning Geotechnics: A Qualitative Approach - Ena Kartina Abdul Rahman; Masitah Shahrill; Sri Kartika A. Rahman (ASEAN Journal of Science and Engineering Education, 2023)
This study aims to examine students’ conceptions of learning Geotechnics by investigating how selected students perceived learning in the teaching and learning to set an enrolled civil engineering program. In addition, students’ reasons for approaches used in learning Geotechnics and students’ perceptions of the role of the learning environment in studying Geotechnics were also identified. Interviews were conducted with diploma-level students, and two topics, compaction of soils and foundations, were selected to understand the approaches taken by the students in learning Geotechnics. The findings revealed that the interviewed students had more than one conception of learning depending on how the students had experienced the learning environment. Interestingly, these students had an appreciation of higher order conceptions of learning and hence used deeper approaches in acquiring knowledge. HHHHowever, the students still mostly used surface approaches in learning Geotechnics. The findings also indicate that the learning context influenced students’ reasons for approaches used in learning. The students also reported a great preference for laboratory classes as their optimum learning environment.